(untitled) (Bangladesh Journal of Botany, 2023)
This study dealt with the phenological activities like leaf flushing, leaf maturation, leaf fall, flower bud formation, flower bud maturation, flower fall, fruit initiation, fruit color changing and fruit ripening for some plants of Curzon Hall Campus, University of Dhaka in 2019 and 2020. The seasonal cycle of plants however is influenced to the greatest extent by temperature, humidity and the concentration of CO2. Forty individuals were studied from 20 species. These 20 species belong to twelve families. Among these 20 species, 5 species are evergreen and 15 species are deciduous, and 7 species are short trees and 13 species are trees. Variation in some individual plants were observed which belong to the same species and they are close to each other, e.g. in different individuals of Couroupita guianensis Aubl., Mesua nagassarium (Burm. f.) Kosterm. leafing, flowering, fruiting times were different. Some plants shed their leaves in frequent season. The temperature, humidity and concentration of CO2 beside trees were also recorded. Temperature was highest in the month of July and lowest in the month of December. Humidity was also highest in the month of July but lowest in the month of February. The concentration of CO2 was highest in the month of August and lowest in the month of January. The temperature, humidity and CO2 concentration varied from 20.1 - 41.8℃, 37.0 - 88.0%, 435.0 - 713.0 ppm, respectively. From the study, it was found that temperature, humidity and concentration of CO2 are important factors for phenological changes. Bangladesh J. Bot. 52(1): 141-148, 2023 (March)